Conception honnethienne d’une socialisation au service de la démocratie et de la liberté sociale - Charles-Antoine Bachand (Éducation et Socialisation)
This article explores the works of the Frankfurt philosopher Axel Honneth on social freedom. Honneth aimed to create a more comprehensive definition of freedom that is not negative, moral, or strictly legal. He took inspiration from early socialists and aimed to reconcile three revolutionary promises of liberty, equality, and fraternity. Honneth argues that freedom can only be collective and that individual and collective aspirations can only really be fulfilled through mutual cooperation. While autonomy and freedom are commonly accepted as educational goals, Honneth's concept of social freedom allows us to consider autonomy anchored in solidarity. This article will discuss the implications of such a conception of freedom on socialization, including in educational contexts.